Preparation method and application of coffee grounds hydrothermal carbon for removing sulfonamide antibiotics from wastewater
By optimizing the preparation method of iron-based coffee ground hydrothermal carbon, using divalent iron-modified complex ligand structure and active metal sites, combined with hydrothermal reaction and ultrasonic oscillation treatment, iron-based coffee ground hydrothermal carbon catalytic materials with high stability and catalytic performance are prepared, solving the problems of poor stability and low degradation efficiency of carbon-based catalysts in the prior art, and achieving efficient degradation and wide application of sulfonamide antibiotic pollutants.
Patent Information
- Application Number
- CN202410664043.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The existing carbon-based catalysts have poor stability in advanced oxidation systems, and the degradation efficiency of sulfonamide antibiotic pollutants in complex water environments is low, making it difficult to quickly screen and optimized preparation conditions.
By optimizing the preparation method of iron-based coffee ground hydrothermal carbon, using divalent iron-modified complex ligand structure and active metal sites, combined with hydrothermal reaction and ultrasonic oscillation treatment, iron-based coffee ground hydrothermal carbon catalytic material with high stability and catalytic performance is prepared.
It significantly improves the stability and catalytic performance of iron-based coffee grounds hydrothermal carbon, has strong degradation ability to sulfonamide antibiotic pollutants, has a wide range of application, short reaction time, rarely produces by-products, and has strong adaptability.
Smart Images

Figure CN118651840B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of water pollution control, and relates to a preparation method and application of coffee grounds hydrothermal carbon for removing sulfonamide antibiotics from wastewater, and specifically to a preparation method and application of a catalytic material for removing sulfonamide antibiotics pollutants from environmental wastewater by using an optimized iron-based coffee grounds hydrothermal carbon. Background Art
[0002] Sulfonamide antibiotics are widely distributed in various environmental water bodies. Due to their serious bioaccumulation and endocrine disruption, they pose a serious threat to biological and human health. Studies have shown that the presence of such substances can still be detected in water bodies that meet discharge standards. Bioaccumulation and food chain pathways are the key to sulfonamide antibiotics entering the human body and causing irreversible health risks to the human body. Therefore, how to effectively remove sulfonamide antibiotics in water has become one of the hot topics in water pollution treatment research.
[0003] In recent years, the advanced oxidation degradation system based on carbon-based catalyst activated persulfate has been widely studied due to its advantages such as thorough degradation, large specific surface area, excellent porosity, fast degradation rate, long free radical existence time, and low energy consumption. However, due to the poor stability of carbon-based catalysts in complex water environments and the weakening of circulation capacity, the degradation efficiency of sulfonamide antibiotic pollutants in complex water bodies is low due to the disintegration of pollutant molecules. Therefore, maintaining the high stability of the degradation system still faces great challenges.
[0004] Based on hydrothermal reaction, the mass transfer characteristics of the material are optimized, and its high specific surface area is maintained. Ferrous iron can provide good metal active sites and separation holes to maintain better stability and catalytic performance in water pollution control (Science of The Total Environment.2023,914:169-823). In addition, the loading of oxygen-containing functional groups and ferrous iron significantly improves the mass transfer efficiency of pollutants and carbon-based catalysts (Water Research.2024,253:121-265), wherein the loading metal atom modification technology provides metal active sites by embedding metal atoms into carbon-based apertures, while improving the activation ability of the material to persulfate, further improving the contact rate of free radicals with pollutants (Environmental Research.2022,212:113-406). However, another problem is that traditional hydrothermal carbon preparation is mainly prepared under relatively wide reaction time, temperature, pressure, pH and other conditions to prepare different hydrothermal carbon materials, and gradually screen out better preparation conditions by adsorption effect. However, this will consume a lot of manpower and material resources, and the screening time is long, and the optimized preparation scheme cannot be quickly selected. In addition, the basic physical and chemical properties of hydrothermal carbon prepared under different conditions, such as surface area, pore size distribution, thermal stability, characteristic functional group types and contents, vary greatly. Therefore, how to quickly screen and optimize the preparation conditions of iron-based coffee grounds hydrothermal carbon is the basis for ensuring the excellent adsorption and catalytic properties of iron-based hydrothermal carbon. Summary of the invention
[0005] In order to overcome the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a preparation method and application of coffee grounds hydrothermal carbon for removing sulfonamide antibiotics in wastewater.
[0006] The purpose of the present invention is to provide a green, economical, widely applicable, and excellent carbonaceous environmental functional catalyst for the synthesis of green and economical carbon-based catalytic materials in advanced oxidation systems, in order to solve the problems of poor stability of existing carbon-based catalytic materials in advanced oxidation systems and difficulty in screening optimized carbon-based preparation environments.
[0007] The purpose of the present invention is achieved by at least one of the following technical solutions.
[0008] The preparation method and application of coffee grounds hydrothermal carbon for removing sulfonamide antibiotics from wastewater provided by the present invention comprises the following steps:
[0009] (1) The collected coffee grounds powder, wherein the water content of the coffee grounds hydrochar is about 20%, is dried in an electric blast drying oven at 60° C. for 3 hours to ensure that the water content is removed. Then it is crushed and passed through a 60-mesh sieve to separate coarse impurities, and the target coffee grounds powder is retained.
[0010] (2) Take 17 200 mL beakers, wash them thoroughly with deionized water and label the beakers 1 to 17. Use a measuring cylinder to accurately measure 60 mL of deionized water and 40 mL of NaOH, the concentration of which is 0.1 mol / L, into a 200 mL beaker.
[0011] (3) Weigh 4 g of dried coffee grounds powder and a predetermined amount of ferrous chloride. The Fe:C ratio is 1:1, 1:2, and 2:1. After calculation and weighing, place them in the beaker in step (2) at the same time, add 0.1 mol / L sodium hydroxide and an appropriate amount of hydrochloric acid solution, and adjust the pH value of the solution to 5, 7.5, and 10.
[0012] (3) The 17 beakers containing the test solutions were placed in an ultrasonic oscillator for 30 minutes to fully mix them. The 17 samples were then placed in a magnetic stirrer at 25°C and a speed of 800 r / min to fully mix them for 2 hours.
[0013] (4) After stirring, pour the samples in the 17 beakers into 17 hydrothermal reactors respectively, and place them in an electric blast drying oven for hydrothermal reaction at 140℃, 170℃, and 200℃ for 6 hours to fully mix and react according to the corresponding groups generated by DesignExpert. After the reaction, place the hydrothermal carbon samples in a vacuum drying oven and dry them to constant weight. According to the condition combination generated by the Design Expert software algorithm, the samples are numbered 1-17. The corresponding samples are placed in a vacuum drying oven and dried at 60℃ to constant weight to obtain 17 groups of iron-based coffee grounds hydrothermal carbon samples under different pH, hydrothermal temperature, and Fe:C conditions. The catalytic degradation efficiency of each of the 17 groups of samples is fed back to the Design-Expert software, and the Design Expert software algorithm analyzes and draws a response surface to quickly screen and optimize the preparation conditions of Fe-modified coffee grounds hydrothermal carbon.
[0014] Furthermore, the preparation of the optimized iron-based coffee grounds hydrothermal charcoal in step (1) comprises:
[0015] A. The FeCl calculated based on the experimental ratio 2 After being evenly mixed with 60 ml of deionized water, solution A is obtained; then the solution A and the sodium hydroxide solution are slowly dripped into the beaker with coffee grounds added, and the above solution is dripped while stirring in a covered beaker to prevent the divalent iron from being oxidized by air and reducing the activation ability of persulfate, and then the hydrothermal reaction is carried out for 6 hours to fully load more oxygen-containing functional groups to obtain iron-based coffee grounds hydrothermal carbon.
[0016] B. Dry the iron-based coffee grounds hydrothermal carbon in step A at 60° C. in an electric blast drying oven, and cool to room temperature to obtain an iron-based coffee grounds hydrothermal carbon carbonaceous sample.
[0017] Furthermore, the preparation of the optimized iron-based coffee grounds hydrothermal charcoal in step (2) comprises:
[0018] A. Mix the mixture evenly with deionized water and divalent iron to obtain solution A; then drop the solution A and 0.1 mol / L sodium hydroxide solution into a beaker, stir at room temperature for 2 h and transfer to a reactor.
[0019] B. Drying the hydrothermal reaction liquid described in step A in an electric blast drying oven, calcining it, and cooling it to room temperature to obtain an iron-based coffee grounds hydrothermal carbon catalyst.
[0020] Furthermore, the concentration of the NaOH solution in step A is 0.1 mol / L, the mass ratio of the divalent iron to the NaOH solution is 2:30; the FeCl 2 ·4H 2 The mass percentage concentration of the O aqueous solution is 2.1-2.3wt%; the solution A and FeCl 2 ·4H 2 The mass ratio of the O aqueous solution is 1:3.7-3.9; the stirring treatment time is 12-24h; the vacuum drying temperature is 60-65°C, and the vacuum drying time is 10-24h.
[0021] Preferably, the drying method in step A is electric heating air drying.
[0022] Furthermore, the iron-based coffee grounds hydrothermal carbon catalyst obtained in step A has a specific surface area of 800-1600m 2 / g.
[0023] Furthermore, the temperature of the preheating treatment in step B is 60°C-65°C, and the time of the preheating treatment is 10-24h.
[0024] Furthermore, the specific surface area of the iron-based hydrothermal carbon catalyst obtained in step B is 600-1200m 2 / g.
[0025] Furthermore, in step (2), the FeCl 2 FeCl 2 ·4H 2 O, FeCl 2 、FeSO 4 、FeSO 4 7H 2 O; the molar mass and molar concentration of the sodium hydroxide and hydrochloric acid solutions are 0.1:40:1.0:36.5; the temperature of the hydrothermal reaction treatment is 140-200°C, and the water bath heating treatment time is 6-6.1h.
[0026] Preferably, during the preparation of the iron-based coffee grounds hydrothermal charcoal in step (2), the ferrous iron solution A is added dropwise while the sodium hydroxide solution is added dropwise while stirring.
[0027] Furthermore, the temperature of the hydrothermal reaction in step (2) is 140-200°C.
[0028] Preferably, the reaction solution in step (2) does not need to be filtered, but is dried and cooled to room temperature by electric heating and forced air drying, and then the cooled solid is collected.
[0029] Preferably, the pH is adjusted with sodium hydroxide or hydrochloric acid 1-2 times in step (2). Sodium hydroxide and hydrochloric acid can provide a basic environment for hydrothermal reaction.
[0030] The present invention also provides a catalytic material for removing sulfonamide antibiotic pollutants in wastewater using an optimized iron-based coffee grounds hydrothermal carbon prepared by the above-mentioned preparation method. The optimized iron-based coffee grounds hydrothermal carbon is labeled as Fe-SCGs.
[0031] The Fe-SCGs provided by the invention can be used to remove sulfonamide antibiotic pollutants in wastewater.
[0032] The Fe-SCGs provided by the present invention can be used to remove sulfonamide antibiotic pollutants in wastewater, comprising the following steps:
[0033] The Fe-SCGs catalytic material and persulfate for removing sulfonamide antibiotic pollutants in wastewater with a pH value of 3.0-7.0 are added, and then the reaction is shaken at room temperature to obtain treated water with sulfonamide antibiotic pollutants removed.
[0034] Furthermore, the persulfate is one or more of sodium persulfate and potassium persulfate; the molar ratio of the persulfate to the sulfonamide pollutants in the wastewater is 10-75:1; the catalytic material of the optimized iron-based coffee grounds hydrothermal carbon for removing sulfonamide antibiotic pollutants in wastewater is 0.1-0.5g / L; the sulfonamide antibiotic pollutants are one or more of sulfamethoxazole, sulfadiazine, methoxazole, sulfadoxine, sulfaquinazoline, sulfadimethoxine, and trimethoprim; and the oscillation reaction time is 60-240min.
[0035] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0036] (1) The Fe-SCGs preparation method provided by the present invention is simple and has strong reproducibility;
[0037] (2) The catalytic material for removing sulfonamide antibiotic pollutants from wastewater based on Fe-SCGs carbonaceous catalyst provided by the present invention has significantly enhanced stability compared with traditional coffee grounds hydrothermal carbon materials and has a wide range of adaptability to pH;
[0038] (3) The catalytic material for removing sulfonamide pollutants in wastewater based on Fe-SCGs carbonaceous catalyst provided by the present invention has strong degradation ability for sulfonamide antibiotic pollutants and high catalytic efficiency;
[0039] (4) The catalytic material for removing sulfonamide antibiotic pollutants in wastewater based on the Fe-SCGs carbonaceous catalyst provided by the present invention has a wide range of applications and has certain practical application prospects;
[0040] (5) The catalytic material for removing sulfonamide antibiotic pollutants in wastewater based on Fe-SCGs carbonaceous catalyst provided by the present invention has a short reaction time, fast degradation, very little by-product generation, and wide adaptability to wastewater pH during the catalytic degradation of sulfonamide antibiotic pollutants, and has good application prospects.
[0041] In summary, the present invention utilizes divalent iron to modify the complex ligand structure and active metal sites, enhances the stability and catalytic performance of iron-based coffee grounds hydrothermal carbon through hydrothermal reaction, and further improves the material performance through modification and optimization, so that the catalytic material has the ability to efficiently degrade and recycle sulfonamide antibiotic pollutants. The removal efficiency of the material for difficult-to-degrade sulfonamide antibiotic pollutants in complex organic wastewater is significantly enhanced. The material has low operating cost, wide application range, good economic benefits and broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 This is the SEM scanning electron microscope image of the SCGs carbide in Example 1.
[0043] Figure 2 This is the mapping scanning electron microscope image of the Fe-SCGs carbide in Example 2.
[0044] Figure 3 The surface fitting graph was obtained for the Fe-SCGs preparation conditions optimized by the response surface model algorithm in Example 3. DETAILED DESCRIPTION
[0045] The specific implementation of the present invention is further described below in conjunction with examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that if there are processes that are not particularly described in detail below, they can be implemented or understood by those skilled in the art with reference to the prior art. If the manufacturer of the reagents or instruments used is not indicated, they are deemed to be conventional products that can be purchased commercially.
[0046] The present invention mainly uses sulfonamide in organic wastewater as a typical pollutant. The specific implementation of the present invention is further described below by examples, but the embodiments of the present invention are not limited thereto.
[0047] Example 1
[0048] (1) In this example, 4 g of coffee grounds powder was dissolved in 60 mL of deionized water and 40 mL of 0.1 mol / L NaOH solution, with the mass ratio of the coffee grounds powder to the NaOH solution being 1:10. After the mixture was fully mixed, 2 g of FeCl 2 ·4H 2 O(2.1wt%FeCl 2 ·4H 2 O), adjust the solution pH to 10. Then place it on a magnetic stirrer and stir at 25°C for 2h, transfer it to a hydrothermal reactor, and hydrothermally react at 179.7°C for 6h to obtain 6g of iron-modified coffee grounds hydrothermal carbon reaction liquid. After the iron-modified coffee grounds hydrothermal carbon reaction liquid is kept at 60°C in an electric forced air drying oven for 6h, it is naturally cooled to constant weight to obtain an iron-modified coffee grounds hydrothermal carbon sample. The obtained iron-modified coffee grounds hydrothermal carbon carbonaceous catalyst has a 10-40nm layered, tightly connected pore structure and a smooth surface morphology while maintaining the basic morphology of iron-modified coffee grounds hydrothermal carbon. The surface crystal morphology basically maintains a regular cube. The pore structure in the middle is relatively large, which plays a key role in the transfer and coating of sulfonamide antibiotic molecules (such as Figure 1 shown).
[0049] (2) Dissolve 4 g of coffee grounds powder in 0.1 mol / L sodium hydroxide and add 2 g of FeCl 2 ·4H 2 O aqueous solution. The iron-modified coffee grounds hydrothermal carbonization is mixed evenly to make sodium hydroxide: NaOH: ferrous chloride: FeCl 2 ·4H 2 O, coffee grounds powder carbide is 0.1 mol: 7.2 mol: 4 g. After the container is sealed, the hydrothermal reaction is carried out at 179.4°C for 6 hours and then allowed to stand at room temperature. The product after the hydrothermal reaction is transferred to an electric heated blast drying oven, and then vacuum dried at 40°C to obtain 6 g of the catalytic material for removing sulfonamide antibiotic pollutants from wastewater based on iron-modified coffee grounds hydrothermal carbonization. This catalytic material is labeled as Fe-SCGs 179.4 .
[0050] (3) Using a conical flask as a reactor, add 20 mL of a mixed solution of sulfamethoxazole (SMX), wherein the solvent is deionized water, and the concentration of sulfamethoxazole (SMX) in the mixed solution is 5 mg / L. Then add potassium persulfate to the conical flask.2 O 8 The concentration was 20 mM, the volume was 0.2 ml, and 0.1 g of Fe-SCGs prepared in Example 1 at 179.4 °C was added. 179.4 Place the conical flask in a shaker at 150 rpm and react for 240 min at room temperature:
[0051] (4) Step (4) The conditions are basically the same as those in step (3), except that the unmodified coffee grounds hydrothermal carbon, labeled as SCGSHC, is added to the conical flask, and SCGSHC is used instead of Fe-SCGs 179.4 ;
[0052] (5) Step (5) The conditions are basically the same as those in step (3), except that the conical flask is filled with raw coffee grounds carbide, labeled as SCGs, and SCGs carbide is used instead of Fe-SCGs. 179.4 ;
[0053] Fe-SCGs prepared in Example 1 179.4 The degradation parameters of sulfamethoxazole (SMX) by carbide compared with the unmodified coffee grounds hydrochar sample SCGSHC and the original coffee grounds sample SCGs are shown in Table 1. The results show that Fe-SCGs 179.4 The degradation capacity and removal effect of sulfonamide antibiotic pollutants are significantly improved.
[0054] Table 1 Selective removal effect of MIL-100MIP on DEP
[0055] Carbide Name SMX(mg / g) SCGs 10.56 SCGSHC 15.27 Fe-SCGs179.4 30.25
[0056] Example 2
[0057] (1) In this example, 2 g FeCl 2 ·4H 2 O and 4 g coffee grounds powder were dissolved in 40 mL 0.1 mol / L NaOH solution and 60 mL deionized water. 2 ·4H 2The mass ratio of O to NaOH solution is 1:4. 1 mol / L hydrochloric acid solution is gradually added dropwise, the mass fraction of the hydrochloric acid solution is 3.6wt%, and the pH is adjusted to 10. Then, after ultrasonic treatment for 30 minutes, it is placed on a magnetic stirrer and stirred at 25°C for 2 hours, and then transferred to a hydrothermal reactor. The hydrothermal reaction is carried out in an electric blast drying oven at 179.99°C for 6 hours to obtain an iron-based coffee grounds hydrothermal carbon hydrothermal liquid at 179.99°C. The iron-based coffee grounds hydrothermal carbon hydrothermal liquid at 179.99°C is kept at 60°C in an electric blast drying oven for 6 hours, and then naturally cooled to constant weight to obtain an iron-based coffee grounds hydrothermal carbon sample prepared at 179.99°C, which is marked as Fe-SCGSs. 179.99 .
[0058] (2) 2g FeCl 2 ·4H 2 O is dissolved in 40mL of sodium hydroxide (the concentration is 0.1mol / L) and 60mL of deionized water, and hydrochloric acid (the concentration is 1mol / L) is added to the beaker. After being evenly mixed with the coffee grounds powder, ultrasonic treatment is performed for 30 minutes to make sodium hydroxide: hydrochloric acid: coffee grounds powder: NaOH: HCl: SCGs carbide: FeCl 2 ·4H 2 O is 0.1 mol: 1.0 mol: 2.8 mol: 4 g: 2 g; after the container is sealed, the hydrothermal reaction is carried out at 178.7 ° C for 6 hours and then allowed to stand to room temperature to obtain a product after the hydrothermal reaction; the product after the hydrothermal reaction is transferred to an electric heated blast drying oven, and then the product after the hydrothermal reaction is placed at 60 ° C for vacuum drying to obtain 6 g of the catalytic material for removing sulfonamide antibiotic pollutants in wastewater based on iron-modified coffee grounds hydrothermal carbonization, and the catalytic material prepared at 178.7 ° C is marked as Fe-SCGs 178.7 , the material maintains the Fe-SCGs 178.7 The basic characteristic elements of carbides are morphology, content and distribution. Based on the mapping scanning electron microscope image, it can be seen that the surface iron loading effect of iron-modified coffee grounds is the most significant. The iron content loaded inside the pores is small. The small amount of iron elements distributed inside the pores can reduce the blockage of the pores, which is beneficial to the mass transfer of sulfonamide antibiotic molecules. In addition, it also contains trace amounts of S and P elements, which can also promote the occurrence of mass transfer characteristics to a certain extent. The surface-loaded iron improves the electron transfer capacity and the contact area of sulfonamide antibiotic molecules through a large specific surface area and high porosity (such as Figure 2 shown).
[0059] (3) Use a conical flask as a reactor, add 20 mL of SMX (5 mg / L) industrial wastewater, and then add KHS described in potassium persulfate 2 O 8The volume ratio of sulfonamide antibiotics to pollutants was 1:100. 0.1 g of Fe-SCGs prepared in Example 2 was added. 179.99 Place the conical flask in a shaker at 150 rpm and react for 240 min at room temperature. Take samples at fixed points for analysis:
[0060] (4) The conditions of step (4) are basically the same as those of step (3), except that the Fe-SCGs obtained in step (2) is added to the conical flask. 178.7 , using Fe-SCGs 178.7 Substitute for Fe-SCGs 179.99 ;
[0061] (5) Step (5) The conditions are basically the same as those in step (3), except that the original coffee grounds material SCGs is added to the conical flask, and the Fe-SCGs is replaced by SCGs carbide material. 179.99 ;
[0062] SCGs and Fe-SCGs prepared in Example 2 178.7 Carbide materials and Fe-SCGs 179.99 The parameters of the removal and degradation effect of sulfamethoxazole are shown in Table 2. The results show that Fe-SCGs 179.99 The removal rate of sulfonamide antibiotics pollutants is fast, which is better than SCGs and Fe-SCGs. 178.7 The reaction system is more stable.
[0063] Table 2 Effect of various catalytic materials on COD removal and degradation
[0064]
[0065] Example 3
[0066] (1) Take 17 200mL beakers and a high-temperature reactor, wash and dry them with deionized water, and then label the beakers and reactors as 1-17. The reactor and beaker numbers should be kept consistent. Use a measuring cylinder to accurately measure 60mL of deionized water and 40mL of NaOH (0.1mol / L) solution in a 200mL beaker, and weigh 4g of dried coffee grounds powder and a pre-set amount of ferrous chloride, respectively. The Fe:C ratio is 1:1, 1:2, and 2:1. And calculate and weigh the amount of iron according to the ratio. At the same time, place the weighed carbon and iron in a beaker containing 60mL of deionized water and 40mL of 0.1mol / L sodium hydroxide solution, and measure the pH value of the solution at this time.
[0067] (2) Add an appropriate volume of dilute hydrochloric acid, the concentration of which is 1 mol / L, and the solvent is deionized water. Add sodium hydroxide solution, the concentration of which is 0.1 mol / L, and the solvent is deionized water. Make NaOH: sodium hydroxide: hydrochloric acid: HCl: FeCl 2 ·4H 2 O: The carbides under different conditions are 0.1 mol / L: 1 mol / L: 2 g: 4 g. The pH value of the solution in beakers 1, 2, 9, and 11 is adjusted to 5.0; the pH value of the solution in beakers 5, 6, 7, 8, 13, 14, 15, 16, and 17 is adjusted to 7.5; the pH value in beakers 3, 4, 10, and 12 is adjusted to 10.0.
[0068] (3) The 17 beakers with adjusted pH values were placed on a magnetic stirrer and stirred for 2 hours at a stirring temperature of 25° C. and a rotation speed of 800 r / min.
[0069] (4) After stirring for 2 hours, the solutions in the 17 beakers were poured into the corresponding numbered reactors respectively. The reactor numbers were consistent with the beaker numbers. Reactors No. 1, 3, 5, and 7 were placed in a 140°C electric heating blast drying oven; Reactors No. 9, 10, 11, 12, 13, 14, 15, 16, and 17 were placed in a 170°C electric heating blast drying oven; Reactors No. 2, 4, 6, and 8 were placed in a 200°C electric heating blast drying oven for hydrothermal reaction for 6 hours.
[0070] (5) After 6 h of hydrothermal reaction, the hydrothermal liquid in the reactor was poured into beakers numbered 1-17 respectively, and the 17 beakers were placed in an electric blast drying oven and dried at 60 °C for 10-12 h to obtain 17 multi-factor hydrothermal carbon samples under different conditions.
[0071] (6) Add 0.1 g of the Fe-SCGs sample prepared under different conditions in step (5), use a 200 mL conical flask as a reactor, add 20 mL of a sulfonamide antibiotic solution, the solvent is deionized water, and in the mixed solution, the concentration of the sulfonamide antibiotic is 5 mg / L, then add potassium persulfate and sodium persulfate to the conical flask: sulfonamide pollutants = 10:1, the ratio is a volume ratio. Place the 200 mL conical flask in a shaking table at 150 rpm, react at 25° C. for 240 min, and then filter through a 0.45 um filter membrane to obtain the degradation rate of the sulfonamide antibiotics by liquid phase detection.
[0072] (7) The obtained experimental data are fitted to a quadratic polynomial model by computer, which can be expressed as: \[Y=\beta_0+\beta_1T+\beta_2P+\beta_3M+\beta_{12}TP+\beta_{13}TM+\beta_{23}PM+\beta_{11}T^2+\beta_{22}P^2+\beta_{33}M^2\], where \(\beta_i\) is the regression coefficient, which is calculated by computer using the least squares method. The significance and goodness of fit of the model are then evaluated by variance analysis. After checking the F value, P value and R2 value to determine the reliability of the model. The residual plot is further checked to confirm that the assumptions of the model are established, and finally a three-dimensional response surface plot and contour plot are generated to visualize the impact of each variable on the catalytic performance (such as Figure 3 As shown). By analyzing the response surface, the variable combination region with the highest catalytic performance is determined. Mathematical optimization techniques (Lagrange multiplier method or direct search method) are used to find the optimal temperature, pH and iron-carbon ratio of 179.99, 10, and 0.5 under given constraints.
[0073] Fe-SCGs prepared in Example 3 140 、Fe-SCGs 170 、Fe-SCGs 200 Carbide materials and Fe-SCGs 140 、Fe-SCGs 170 、Fe-SCGs 200 The degradation parameters of sulfonamide antibiotics under different pH conditions are shown in Table 3. The results show that Fe-SCGs has good catalytic performance and stability in the pH range of 7.5-10 and has a wide range of applications.
[0074] The degradation parameters of the Fe-SCGs carbon catalysts prepared under different conditions in Example 3 and the Fe-SCGs prepared under different conditions on sulfonamide antibiotics are shown in Table 3. The results show that the optimized ratio of Fe-SCGs activated persulfate has a certain degradation performance on sulfonamide, and the removal effect is significantly improved in the alkaline range. The acidic environment inhibits the generation rate of free radicals in the reaction system to a certain extent.
[0075] Table 3 Removal effect of Fe-SCGs on sulfonamide
[0076]
[0077]
[0078] The inventors need to explain that any changes, substitutions, modifications, etc. made by those skilled in the art without departing from the spirit of the present invention should fall within the scope of disclosure and protection of the present invention.
Claims
1. A coffee grounds hydrothermal carbon for removing sulfonamide antibiotics from wastewater, characterized in that: The coffee grounds hydrothermal carbon is an iron-modified coffee grounds hydrothermal carbon catalyst, having a 10-40 nm layered tightly connected pore structure and a smooth surface morphology. The surface crystal morphology maintains a regular cube, and the pore structure in the middle is large, which is used to achieve the transfer and coating of sulfonamide antibiotic molecules. The coffee grounds hydrothermal carbon utilizes divalent iron to modify the complex ligand structure and active metal sites, and enhances the stability and catalytic performance of the iron-based coffee grounds hydrothermal carbon through a hydrothermal reaction, so that the catalytic material has the ability to efficiently degrade and recycle sulfonamide antibiotic pollutants. The preparation method thereof comprises the following steps: Step 1, drying and cooling the coffee grounds, and then crushing and screening them; Step 2, weigh 4g of coffee grounds powder, and then weigh the mass of ferrous chloride according to the Fe:C mass ratio of 1:1, 1:2, and 2:1; mix FeCl2•4H2O with 60 mL of deionized water to obtain solution A, and then slowly drop the solution A and sodium hydroxide solution into the beaker with coffee grounds to generate flocs for surface loading; then use a covered beaker to drop the above solution while stirring to prevent the divalent iron from being oxidized by air to reduce the activation ability of persulfate, so that more oxygen-containing functional groups can be fully loaded on the carbon-based surface; the concentration of sodium hydroxide is 0.1 mol / L, and the solvent is deionized water; after fully stirring and mixing, 17 mixed stock solutions are obtained, the pH value of the stock solution is measured, and a certain amount of hydrochloric acid and sodium hydroxide solution are appropriately added to the 17 stock solutions to adjust the pH value to 5, 7.5 and 10; The concentration of the NaOH solution is 0.1 mol / L, which is used to prevent excessive alkalinity from dissolving the sample and causing pore size collapse; The molar concentration and molar mass of the sodium hydroxide solution and the hydrochloric acid solution are respectively: 0.1, 40, 1.0, 36.5; Step 3, mixing the 17 stock solutions obtained in step 2 after adjusting the pH; Step 4: Pour the liquids in the 17 beakers into 17 hydrothermal reactors respectively, and place them in a drying oven for hydrothermal reaction at 140 ℃, 170 ℃, and 200 ℃ for 6 h to fully mix and react according to the corresponding groups generated by Design Expert; dry the hydrothermal reaction liquid in a drying oven to constant weight; label the samples 1-17 according to the condition combinations generated by the Design Expert software algorithm, and place the corresponding beakers in a drying oven and dry them at 60 ℃ to constant weight to obtain 17 groups of samples under different pH, hydrothermal temperature, and Fe / C conditions, which are marked as Fe-SCGs; The iron-based coffee grounds hydrothermal charcoal is dried in an electric heated air drying oven and then cooled to room temperature; Step 5, adding 0.1 g of the 17 groups of Fe-SCGs samples obtained in step 4 to the wastewater to perform a degradation experiment on sulfonamide antibiotics, and obtaining the degradation rate of sulfonamide antibiotics by Fe-SCGs of each group of samples; Step 6, the degradation efficiency of each of the 17 groups of Fe-SCGs samples was fed back to the Design-Expert software to generate a three-dimensional response surface plot and contour plot to visualize the effect of each variable on the catalytic performance. By analyzing the response surface, the variable combination region with the highest catalytic performance was determined, and the optimal Design Expert software algorithm was used to analyze and draw the response surface to quickly screen and optimize the preparation conditions of Fe-modified coffee grounds hydrothermal carbon.
2. The coffee grounds hydrothermal charcoal according to claim 1, characterized in that: Step 2 also includes: Step (1), take 17 200 mL beakers numbered 1-17, and perform the following steps on the pretreated samples No. 1-17; Step (2), accurately measure 60 mL of deionized water and 40 mL of NaOH solution into a 200 mL beaker using a measuring cylinder to obtain a NaOH dilution solution; Step (3), weigh 4 g of dried coffee grounds powder and place it in the diluted NaOH solution obtained in step (2) and stir evenly; Step (4), weighing ferrous chloride and coffee grounds according to the Fe:C mass ratio, and placing them in the mixed solution obtained in step (3) and stirring and mixing them again; Step (5), determining the pH value of the solution obtained in step (4) and appropriately adding 1 mol / L hydrochloric acid and 0.1 mol / L sodium hydroxide solution to adjust the pH values of the solutions in the 17 beakers to reach the aforementioned pH values.
3. The coffee grounds hydrothermal charcoal according to claim 1, characterized in that: The volume ratio of the deionized water to the NaOH solution is 3:2; The mass percentage concentration of the FeCl2•4H2O aqueous solution is 3-13%; The mass ratio of the solution A to the prepared FeCl2•4H2O aqueous solution is 1:4-8; The stirring time is 0.5-2 h; The temperature of the hydrothermal reaction is 140-200° C., and the time of the hydrothermal reaction is 6-7 h.
4. The coffee grounds hydrothermal charcoal according to claim 1, characterized in that: The temperature in the electric blast drying oven is 60°C-65°C, which is 3:7-10 compared to the temperature when preparing hydrothermal charcoal, and the treatment time is 10-24 h.
5. The coffee grounds hydrothermal charcoal according to claim 1, characterized in that: Step 5 also includes: Add 0.1 g of the prepared Fe-SCGs sample, use a 200 mL conical flask as a reactor, add 20 mL of sulfonamide antibiotic solution, the solvent is deionized water, in the mixed solution, the concentration of sulfonamide antibiotic is 5 mg / L, and then add potassium persulfate or persulfate: sulfonamide pollutants in a volume ratio of 100:1 into the conical flask; place the conical flask in a shaking table at 150 rpm, react at 25 ° C for 240 min, and then pass through a 0.45 um filter membrane and use liquid phase detection to obtain the degradation rate of sulfonamide antibiotics.
6. Use of the coffee grounds hydrothermal carbon for removing sulfonamide antibiotics from wastewater as claimed in any one of claims 1 to 5 as a catalytic material in removing sulfonamide antibiotic pollutants from wastewater.
Citation Information
Patent Citations
Preparation method for biomass-based magnetic hydrothermal charcoal
CN110422887A
Preparation method and application of coffee grounds hydrothermal carbon adsorbent
CN110773124A